The effect of gene tubC on the vegetative growth of benomyl-resistant strains of Aspergillus nidulans - Andrade-Monteiro, Cristina; Pombeiro-Sponchiado, Sandra R. C. [UNESP]; Martinez-Rossi, Nilce M. (Oxford University Press (OUP), 1994)
Two benomyl-resistant mutants, benD3 tubC41 and benD4 tubC42, of Aspergillus nidulans were isolated after UV treatment. The tubC mutations permitted good conidiation of these strains in culture media containing benomyl and were responsible for increasing their benomyl resistance levels. This implies that β3-tubulin, a product of the tubC gene, in addition to being involved in fungal conidiation, participates in the vegetative growth of the fungus. The tubC gene was located in linkage group I.
Keywords: β-tubulin; Aspergillus nidulans; Benomyl resistance; Conidiation; tubC gene; benomyl; fungicide; tubulin; aspergillus nidulans; drug resistance; fungus growth; fungus mutant; nonhuman; priority journal; Aspergillus; Emericella nidulans; Fungi